Prediction of the chronicity of inflammatory diseases of the urinary system in children - H.O. Lezhenko; N.A. Zakharchenko (Zaslavsky O.Yu., 2023)
Background. The purpose was stratification of factors that lead to the chronicity of inflammatory diseases of the urinary system in children, as well as creation of a mathematical model for predicting their course. Materials and methods. The research group consisted of 97 children (average age - 10.0 ± 1.3 years). The main group was divided into subgroups: the first one - 43 children with acute urinary tract infections (UTIs), the second one - 34 patients with chronic UTIs. The control group consisted of 20 conditionally healthy children. The content of 1,25(OH)2D3, vitamin D-binding protein, inducible nitric oxide synthase (NOS2), cystatin C, cathelicidin, hepcidin, lactoferrin, interleukins 6, 15 was investigated by immunoenzymatic analysis. The impact of factor characteristics on the process of UTI chronicity was evaluated using factor and cluster analyses. A logistic regression equation was used to predict the probability of developing chronic UTIs. The quality of the constructed model was assessed by its sensitivity and specificity, and receiver operator characteristic (ROC) analysis was also used. Results. It was found that 6 factors had the greatest significance: the factor of functional disorders of the urinary tract, the factor of comorbid conditions, the protective factor, the immune factor, chronic foci of the disease, and the NOS2 factor. According to the results of logistic regression, the model for predicting the probability of developing chronic UTI in children had the form of an equation that included 6 variables (early manifestation of the disease, vitamin D level, vesicoureteral reflux, dysmetabolic nephropathy, neurogenic bladder, UTI in the mother in childhood). The classification ability of the model was determined based on the data of the training sample and was 75.0 %. The sensitivity of the model was 78.3 %, and the specificity was 76.5 %. The area under the ROC curve that corresponded to our mathematical model was equal to 0.776. The Gini index was 55.2 %, which corresponds to the good quality of the model. Conclusions. The process of chronicity of the inflammatory process in the urinary system in children occurs under the conditions of the interaction of some pathological factors. The leading risk factors for the chronicity of the inflammatory process are the presence of functional disorders of the urinary tract, early manifestation of the disease, the level of vitamin D, intestinal dysfunction, and the presence of UTI in the mother in childhood.